2022
DOI: 10.1080/21645515.2022.2043102
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of vaccine hesitancy attitudes and social influence as predictors of COVID-19 vaccine uptake in the US

Abstract: Background In many countries with high levels of COVID-19 vaccine access, uptake remains a major issue. We examined prospective predictors of COVID-19 vaccine uptake in a United States longitudinal study. Methods An online longitudinal study on COVID-19 and well-being assessed vaccine hesitancy attitudes, social norms, and uptake among 444 respondents who had completed both survey waves in March and June 2021. Results The mean sample age was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 66 publications
7
21
0
Order By: Relevance
“…The present study elucidated interesting trends across sexual orientation for the perceived likelihood of receiving the COVID-19 vaccine. Our multivariate logistic regression analysis yielded similar findings to previous literature as individuals who reported lower income (heterosexual respondents) and education levels (heterosexual and sexual minority respondents) were less likely to report being likely to receive the COVID-19 vaccine [ 29 , 30 , 31 , 32 , 33 ]. This illustrates an important area of concern and intervention for vaccine education and promotion, given individuals of lower socioeconomic status have the highest risk for poor respiratory health [ 34 ].…”
Section: Discussionsupporting
confidence: 84%
“…The present study elucidated interesting trends across sexual orientation for the perceived likelihood of receiving the COVID-19 vaccine. Our multivariate logistic regression analysis yielded similar findings to previous literature as individuals who reported lower income (heterosexual respondents) and education levels (heterosexual and sexual minority respondents) were less likely to report being likely to receive the COVID-19 vaccine [ 29 , 30 , 31 , 32 , 33 ]. This illustrates an important area of concern and intervention for vaccine education and promotion, given individuals of lower socioeconomic status have the highest risk for poor respiratory health [ 34 ].…”
Section: Discussionsupporting
confidence: 84%
“…In addition, the study found that those in the lowest household income bracket showed a decrease in knowledge regarding the protection and reduction of COVID-19 transmission, while other variables were not statistically significant. This finding is supported by the work of Latkin et al, which found that income was an independent predictor of reduced vaccine uptake and increased hesitancy (38). Latkin et al also demonstrated that political conservatism was associated with reduced vaccine uptake and hesitancy.…”
Section: Demographics That Need More Attention During Interventionsmentioning
confidence: 68%
“…Regarding knowledge, those in the age range between 25-34 and 45-54 showed no improvement post-intervention regarding COVID-19 vaccine side effects. Those in the age range [35][36][37][38][39][40][41][42][43][44] showed decreased knowledge in this variable post-intervention. Interestingly, Gravelle et al reported that individuals aged 25-49 were the group most hesitant towards vaccination and associated this age range with those who are most likely to be parents (36).…”
Section: Demographics That Need More Attention During Interventionsmentioning
confidence: 99%
“…Existing research has identified a set of themes that inform COVID-19 vaccination practices across countries. First, pre-existing attitudes regarding vaccinations shape stances towards a COVID-19 vaccine, both in favour of getting vaccinated [6] and for those who report hesitation [1] , [21] .…”
Section: Background and Contextmentioning
confidence: 99%